Water security: old concepts, new package, what value? - Lautze, Jonathan F.; Manthrithilake, Herath (Wiley, 2012)
"Water security? has come to infiltrate prominent discourse in the international water and development community, and achieving it is often viewed as a new water sector target. Despite the levated status that the concept has increasingly acquired, understandings of the term are murky and quantification is rare. To promote a more tangible understanding of the concept, this paper develops an index for evaluating water security at a country level. The index is comprised of indicators in five components considered to be critical to the concept: (i) basic needs; (ii) agricultural production; (iii) the environment; (iv) risk management; and (v) independence. Achieving water security in these components can be considered necessary but insufficient criteria to measure the achievement of security in related areas such as health, livelihoods, and industry. After populating indicators with data from Asia-Pacific countries, results are interpreted and the viability of methods is discussed. This effort comprises an important first step for quantifying and assessing water security across countries, which should spur more concrete understanding of the term and discussion of its added value.